2003
DOI: 10.1111/j.1349-7006.2003.tb01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of overexpression of metallothionein in mouse urinary bladder focal lesions induced by treatment with N‐butyl‐N‐(4‐hydroxybutyl)‐nitrosamine

Abstract: Metallothionein (MT) is expressed in various types of human tumors, including transitional cell carcinomas of the urinary bladder, but its biological significance remains unclear. In the present study, the role of MT in urinary bladder carcinogenesis induced by N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) treatment was investigated using C57BL/6 mice. One hundred 5-week-old male C57BL/6 mice were divided into two groups, which were given drinking water with or without 0.05% BBN throughout the experimental perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Metallothionein overexpression in ESCC is often positively correlated with the metastatic and proliferative activities of the cancer (36). In animal tumor models, overexpression of metallothionein has been shown in chemically induced rat and mouse bladder tumors (39,40). Our results show that metallothionein overexpression occurs in precancerous zinc-deficient esophagus (Tables 1 and 2; Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Metallothionein overexpression in ESCC is often positively correlated with the metastatic and proliferative activities of the cancer (36). In animal tumor models, overexpression of metallothionein has been shown in chemically induced rat and mouse bladder tumors (39,40). Our results show that metallothionein overexpression occurs in precancerous zinc-deficient esophagus (Tables 1 and 2; Fig.…”
Section: Discussionsupporting
confidence: 57%
“…In one study, greater MT expression was observed in proliferating tumour cells whereas apoptotic sites within the tumour were associated with lower levels of MT expression. 119 In other studies, MT expression was increased in high grade tumours, and, furthermore, increased MT expression correlated with reduced overall survival and reduced disease-free survival and resistance to chemotherapeutics. 120-123 It also appears that upregulation of different isoforms of MT can occur during tumour progression.…”
Section: Cancer Of the Urinary Tractmentioning
confidence: 75%
“…2). Carcinomas were classified into transitional cell carcinoma (TCC) and squamous cell carcinoma (SCC) (22). The liver and kidney were fixed with 10% formalin, embedded in paraffin blocks and processed routinely for histopathological examination.…”
Section: Methodsmentioning
confidence: 99%